PENATAAN KURIKULUM DALAM PEMBENTUKAN MORAL SISWA - Azhar (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2022)
The curriculum is a set of educational guidelines, but has not responded to the moral formation in the curriculum components. The formation of human moral quality as a basic element of personality needs to be restructured spiritual competence in the curriculum. Jackson and Geckeis in their idea of ​​a curriculum have not included the measurement of spiritual competence. This fact can be found in schools. This paper aims to describe the arrangement of the curriculum in the moral formation of students. Quantitative data is presented in the form of tabulations and graphs to measure curriculum competence. Based on the study and analysis found three main topics. First, the urgency of structuring the curriculum, second, morals in the discussion, third, forming the morale of students, and fourth, strategic steps for structuring the curriculum and integrated solutions. This study is considered new because it uses curriculum structuring in responding to student morale. These findings can be used to strengthen the relevance of the curriculum to the moral decadence of the global era. A curriculum that is not well organized will produce graduates with low affective abilities.